EFEKTIVITAS KERJA PEGAWAI PADA DINAS PERPUSTAKAAN DAN ARSIP DAERAH KABUPATEN KEPULAUAN TALAUD - LALOMPOH, SOLEMAN; PANGKEY, MASJE SILIJA; RARES, JOYCE JACINTA (Sam Ratulangi University, 2019)
Today's technological development increasingly demands the importance of information for everyorganization, both government and private, because basically the whole part of the organization requirestraining as a supporting process of administrative work and the implementation of management functions,and planning, determining the realization of organizational goals. The objective cannot be realized withoutan active role and the accuracy of work or effectiveness of employees, even though the tools owned by theagency are so sophisticated, the sophisticated tools owned by the agency have no benefit to the agency, if therole is not included. Managing employees is difficult and complex, because they have heterogeneousthoughts, feelings, status, and background that are under the organization. The purpose of this study is tofind out the Work Effectiveness of employees at the Regional Library and Archives Service Office of theTalaud Islands Regency. The theory used is Work Effectiveness. The research method used is a qualitativeresearch method to find answers to questions related to Employee Work Effectiveness. These questionsrequire answers that are descriptive in nature that describe the facts about the problems being investigatedas there are rational interpretations of various findings in the field while analyzing all the conditions in thelocation of the study. Based on the results of the study, the work effectiveness of employees at the Libraryand Archives Office of the Talaud Islands Regency, is still experiencing problems such as employees whoare still less consistent in managing time, as well as facilities that are still lacking and human resources arestill poor, so the work is still not fully effective and efficient.Keywords: Effectiveness, Work, Employees